The Ayurvedic Management of Vataja Gulma (AYUSHDHARA, 2025)
Gulma is the disease described specifically among eight diseases in Nidana sthana of Charak Samhita. Although, the symptoms are commonly found in patients, still diagnosis of Gulma is rarely made. The disease has itself so many variations in their symptoms that they cause confusion in diagnosis. But on careful examination and proper knowledge of the disease, it is found that so many people suffer from the disease. This is the reason why our Samhitakaras have given so much attention to it. An attempt has been made to properly manage Vataja Gulma through Ayurvedic system of medicine. Case: Present case study deals with a male patient of age 25 years, suffering from on and off pain all over the abdomen and chronic constipation. Treatment: Patient is treated with Dipana, Pachana, external Abhyanga and Sarvanga Swedana, Shodhana through Virechana after 7 days internal Snehapana and lastly Shamana drugs are given. Results: After treatment, patient got significant relief from the pain and easy bowel evacuation with no recurrence thereafter. Conclusion: From the above study it can be concluded that Vataja Gulma can be managed successfully.